A toll-based bi-level programming approach to managing hazardous materials shipments over an intermodal transportation network. (August 2016) - Assadipour, Ghazal; Ke, Ginger Y.; Verma, Manish
Highlights: We study toll-setting to regulate hazmat shipments through intermodal terminals. A bi-level bi-objective optimization model is proposed. A hybrid solution method viz., PSO that integrates with CPLEX is proposed. Problem instances based on the infrastructure of a railroad operator is studied. Pragmatism and efficiency of the toll-setting policy is demonstrated. Abstract: This research proposes a bi-level bi-objective model to regulate the usage of rail intermodal terminals for hazardous materials (hazmat) shipments, where government imposes tolls to deter carriers from using certain terminals. The complexity of the resulting mathematical program motivates the development of a hybrid speed-constrained multi-objective particle swarm optimization algorithm, which is then integrated with CPLEX, to solve the model. Through a real problem instance based on the intermodal service chain of Norfolk Southern in US, the toll-setting model is examined and further compared with a regular network design approach, in which certain terminals are closed to hazmat containers. The computational results show that the toll-setting policy is more practical and efficient, and the two models can be combined as a two-stage strategy in long-term hazmat transportation regulations. Additional managerial insights are derived for different stakeholders.